Implemetation of motivation factor towards the achievement of Besut Land Office’s employees / Mohamad Aiman Fadhli Baharudin - Baharudin, Mohamad Aiman Fadhli (Faculty of Business and Management, 2013)
This paper is purposely conducted to identify which factors that affect the most employee motivation toward achievement at Besut Land Office. This paper was constructed based on the literature and this study was to help the organization to improve their achievement. There are 3 hypotheses were build based on the literature and the model were tested in previous studies and literature. Motivation is crucial for the organization success that can change the employees‟ way of work. The comparison between motivated people with unmotivated person can be observed or can be judge through the evaluation or the quality of work. To increase level of achievement in the organization, it needs to continuously motivate their employees through appropriate factors or method that must be aligned with the current situation. Thus, the upper level management should take necessary measure to keep their employees motivated for the organization to have great achievement. A sample of 107 employees working in different department of Besut Land Office were selected that all employee have a different job position, wages range, education, and family background. This paper focuses on the practice of the 3 factors, work life balance, training and feedback toward the achievement. The employees should know what is best for them in order to have a better quality of work and indirectly have a better life.